Evaluation of the reach and utilization of the American College of Lifestyle Medicine’s Culinary Medicine Curriculum - Staffier, Kara Livingston; Holmes, Shannon; Karlsen, Micaela Cook; Kees, Alexandra; Shetty, Paulina; Hauser, Michelle E. (Frontiers in Nutrition, 2024)
Introduction Despite the growing interest in “food as medicine,” healthcare professionals have very limited exposure to nutrition as part of their training. Culinary medicine (CM), an evidence-based field integrating nutrition education with culinary knowledge and skills, offers one approach to fill this training gap. The American College of Lifestyle Medicine published a complimentary Culinary Medicine Curriculum (CMC) in 2019, and the objective of this study is to evaluate its reach and utilization, as well as to collect feedback from users. Methods Individuals who downloaded the CMC prior to March 1, 2022 (N=6,162) were emailed an invitation to participate in an online, cross-sectional survey. The survey included both multiple choice and free-text questions about whether CM sessions were conducted, if and how the CMC was used, if and how it was modified for use, and additional requested resources. Free-text responses were inductively coded, and quantitative data was summarized using descriptive statistics. Results A total of 522 respondents provided consent, indicated that they had downloaded the curriculum, and completed the survey. Of the 522, 366 (70%) reported that they had not led or created any CM sessions. The top-reported reason for not leading a session was lack of time (29%). The remaining respondents who did create a CM session did so across various settings, including academic, clinical, coaching, and other settings, and a variety of professionals delivered the CMC sessions, including physicians (50%), registered dietitian nutritionists (30%), and chefs (25%). The majority of respondents (81%) modified the CMC in some way, with many using the curriculum for guidance or ideas only. Patient education materials (66%) and cooking technique instruction videos (59%) were among top requested resources. Discussion The CMC is a versatile resource that can be successfully adapted for use across various settings and by various types of health professionals and practitioners. Future research should investigate whether training in CM results in improved health outcomes for patients/clients. The curriculum will continue to grow to address the needs of users by expanding to include more digital content such as curriculum videos and cooking technique videos.